Reporting of Physical Activity Device Measurement and Analysis Protocols in Lifestyle Interventions. Issue 6 (November 2021) - Jake-Schoffman, Danielle E.; Silfee, Valerie J.; Sreedhara, Meera; Rosal, Milagros C.; May, Christine N.; Lopez-Cepero, Andrea; Lemon, Stephenie C.; Haughton, Christina F.
This systematic review examined the extent to which lifestyle physical activity interventions that used wearable devices (eg, pedometers, accelerometers) reported on the length of device wear time requested in their protocols, criteria for analytic inclusion of data, and participant compliance with device use protocols. Literature were searches were conducted using PubMed, Cochrane Central Register, and PsychInfo. Studies were included if they were the main outcomes paper of a trial that reported on a randomized or quasi-randomized trial focused on increasing lifestyle physical activity and were published between January 1, 2006 and March 30, 2016. Titles and abstracts were screened by 2 independent reviewers; eligible full texts were retrieved and reviewed by 2 independent reviewers. A total of 104 studies used wearable devices (n = 57 pedometers, n = 47 accelerometers). Most studies (n = 65, 67.3%) asked participants to wear devices for 7 days. Almost half of the studies (n = 46, 44.2%) did not report minimum device wear time required for analytic inclusion of data, and variation existed among studies reporting these criteria. Most studies (n = 60, 57.7%) did not report average device wear time, or participant compliance with device wear. Overall, there was heterogeneity in reporting of physical activity device data. Refinement and streamlining of guidelines for device use, analysis, and reporting of data could improve comparability across studies.